As quatro faces de Rodrigo Sanches - Barroca, Mário Jorge (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Rodrigo Sanches, bastard son of king Sancho I, died in 1245 in the first battle of the Civil War of 1245-48. His monument was commissioned by his sister, D. Constança Sanches, and executed in Coimbra c. 1263-64. The cenotaph was removed, in 1626, to the Cloister of the monastery of Grijó, and placed in an arcosolium, which only allowed the reading of the lid and the left side of the sarcophagus. Recently, it was removed to a chapel in the Cloister. For the first time in nearly 400 years, we can now analyze the iconography of the four faces of the monument. We present, here, our first reflection.